THU0252 HORMONE DEPENDENCE AND CANCER IN SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Cobo-Ibáñez, Tatiana; Urruticoechea-Arana, Ana; Rua-Figueroa, Iñigo; Martin-Martinez, Maria Auxiliadora; Ovalles, Juan; Galindo-Izquierdo, María; Calvo-Alen, Jaime; Olive, Alejandro; Fernandez-Nebro, Antonio; Menor-Almagro, Raúl; Muriel, Eva Tomero; Horcada, Loreto; et al.
Abstract : Objectives: To estimate the incidence of cancer in systemic lupus erythematosus (SLE) patients and to analyze factors associated with cancer differentiating between hormone-sensitive (HS) and non-HS cancers. Methods: Multicenter retrospective study of a cohort of patients included in Spanish Society of Rheumatology Lupus Registry (RELESSER). The first cancer after the diagnosis of SLE, sociodemographic, clinical, activity, cumulative damage, severity, comorbidity, treatments, and refractory disease data were collected. Cancers were classified into HS (prostate, breast, endometrial and ovarian) and non-HS (the rest). Standardized incidence ratio (SIR) was calculated and logistics regression models were constructed to identify factors associated with cancer. Results: We included 3539 patients (90.4% women) with SLE (ACR-97 criteria), of whom 154 had cancer (91% women), and 44 were HS (100% women). The SIR for cancer was 1.37 (95% CI: 1.15-1.59), reaching higher values in women under 65 years [2.38 (95% CI: 1.84-2.91)]. The SIR in women with cancer HS vs. non-HS was 1.02 (95% CI: 0.13-1.91) and 1.93 (95% CI: 0.98-2.89)], respectively. In HS vs. non-HS cancers, age at diagnosis of SLE [Odds ratio (OR) 1.04 (p = 0.002) vs. 1.04 (p = 0.019), respectively] and the evolution time [OR 1.01 (p <0.001) vs. OR 1.00 (p = 0.029), respectively] were factors associated with cancer. SLICC/ACR damage index [OR 1.27 (p = 0.022)] and Angiotensin-Converting Enzyme (ACE) inhibitors prescription [OR 2.87 (p = 0.048)] were associated with non-HS cancers. Conclusion: The incidence of cancer in patients with SLE is increased compared to the Spanish population, specially in younger women. This increase might be due to non-HS cancers. SLE with more cumulative damage and more prescription of ACE inhibitors might associate with non-HS cancers. Disclosure of Interests: Tatiana Cobo-Ibáñez: None declared, ANA URRUTICOECHEA-ARANA: None declared, Iñigo Rua-Figueroa: None declared, Maria Auxiliadora Martin-Martinez: None declared, Juan Ovalles: None declared, María Galindo-Izquierdo: None declared, Jaime Calvo-Alen: None declared, Alejandro Olive: None declared, Antonio Fernandez-Nebro: None declared, Raúl Menor-Almagro: None declared, Eva Tomero Muriel: None declared, Loreto Horcada: None declared, Esther Uriarte Isacelaya: None declared, Victor Martinez Taboada: None declared, José Luis Andreu: None declared, Alina Boteanu: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Cristina Bohorquez: None declared, Carlos A. Montilla-Morales: None declared, Gregorio Santos Soler: None declared, Blanca Hernández-Cruz: None declared, Paloma Vela-Casasempere Grant/research support from: UCB, Abbvie, Pfizer, Roche, Bristol-Myer-Squibb (another research, not BIOBADASER related), Consultant for: UCB, Lilly, Pfizer, Roche, Bristol-Myer-Squibb, Speakers bureau: Roche, UCB, MSD, Pfizer, GSK, BMS, Lilly, Eva Salgado Perez: None declared, Mercedes Freire González: None declared, José A Hernandez Beriain: None declared, Elvira Diez Alvarez: None declared, Lorena Expósito: None declared, Olaia Fernández- Berrizbeitia: None declared, Jose Luis Marenco Speakers bureau: abbie, pfizer, novartis, janmsen, Jose M Pego-Reigosa: None declared